STRATEGI GURU DALAM MENERAPKAN PENDEKATAN DEEP LEARNING PADA MATERI PENJUMLAHAN DAN PENGURANGAN BERSUSUN - Solehatinmuffaroh Solehatinmuffaroh; Zainal Zainal (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT This study aims to describe teachers' strategies in implementing the deep learning approach in teaching addition and subtraction with the vertical algorithm method in Grade 2 at SDI Darul Ulum. The study was motivated by mathematics instruction that still tends to focus on procedural aspects, resulting in students' conceptual understanding not being optimally developed. The deep learning approach was chosen because it emphasizes meaningful learning, active student engagement, and reflective thinking skills in line with the implementation of the Merdeka Curriculum. This research employed a qualitative method with a case study design. Data were collected through classroom observations, in-depth interviews, and learning documentation. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing to obtain a comprehensive description of the instructional strategies implemented by the teacher. The findings revealed that the teacher applied various instructional strategies, including the use of concrete learning media, reflective questioning, context-based collaborative learning, dialogic formative feedback, and simple reflection activities. These strategies helped students develop a deeper understanding of addition and subtraction concepts and increased their engagement in the learning process. The findings highlight that the implementation of a deep learning approach in elementary mathematics education can serve as an alternative instructional strategy to support conceptual understanding and active student participation in accordance with their cognitive developmental stage. ABSTRAK Penelitian ini bertujuan mendeskripsikan strategi guru dalam menerapkan pendekatan deep learning pada pembelajaran penjumlahan dan pengurangan bersusun di kelas 2 SDI Darul Ulum. Penelitian dilatarbelakangi oleh pembelajaran matematika yang masih cenderung berfokus pada prosedur sehingga pemahaman konseptual siswa belum berkembang secara optimal. Pendekatan deep learning dipilih karena menekankan pembelajaran bermakna, keterlibatan aktif siswa, dan kemampuan berpikir reflektif sesuai implementasi Kurikulum Merdeka. Penelitian menggunakan metode kualitatif dengan desain studi kasus. Pengumpulan data dilakukan melalui observasi, wawancara mendalam, dan dokumentasi pembelajaran. Data dianalisis melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan untuk memperoleh gambaran menyeluruh mengenai strategi pembelajaran yang diterapkan guru. Hasil penelitian menunjukkan bahwa guru menerapkan strategi pembelajaran melalui penggunaan media konkret, pertanyaan reflektif, pembelajaran kolaboratif berbasis konteks, umpan balik formatif dialogis, dan kegiatan refleksi sederhana. Strategi tersebut membantu siswa memahami konsep penjumlahan dan pengurangan secara lebih mendalam serta meningkatkan keterlibatan siswa dalam proses pembelajaran. Temuan penelitian menegaskan bahwa penerapan pendekatan deep learning pada pembelajaran matematika sekolah dasar dapat menjadi alternatif strategi pembelajaran yang mendukung pemahaman konseptual dan partisipasi aktif siswa sesuai tahap perkembangan kognitif mereka.